2016
DOI: 10.1111/apt.13718
|View full text |Cite
|
Sign up to set email alerts
|

The GerdQ questionnaire and high resolution manometry support the hypothesis that proton pump inhibitor‐responsive oesophageal eosinophilia is a GERD‐related phenomenon

Abstract: GERD, as assessed by GerdQ and high resolution manometry is common in patients with PPI-REE, which may share similar pathogenic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
0
34
0
2
Order By: Relevance
“…However, Savarino et al . showed that PPI‐REE has more frequently clinical, endoscopic, and manometric features similar to those of GERD patients . Furthermore, Podboy et al .…”
Section: Interaction Between Eoe Gastro‐esophageal Reflux Disease Amentioning
confidence: 95%
See 1 more Smart Citation
“…However, Savarino et al . showed that PPI‐REE has more frequently clinical, endoscopic, and manometric features similar to those of GERD patients . Furthermore, Podboy et al .…”
Section: Interaction Between Eoe Gastro‐esophageal Reflux Disease Amentioning
confidence: 95%
“…25,26 However, Savarino et al showed that PPI-REE has more frequently clinical, endoscopic, and manometric features similar to those of GERD patients. 27 Furthermore, Podboy et al have suggested that EoE patients have earlier onset of symptoms (29 versus 38 years), and, using xray barium swallow (which is more sensitive than endoscopy in order to detect a decrease in wall compliance), that they have more frequently long strictures (>8 cm, 51% versus 18% of patients), and a trend toward developing these long segment strictures after 20 years of dysphagia duration (73% versus 30%). 28 Regarding the classical endoscopic features, PPI-REE shows no difference from EoE.…”
Section: Interaction Between Eoe Gastro-esophageal Reflux Disease Amentioning
confidence: 99%
“…1 The authors report that typical features of reflux disease were indistinguishable between GERD and PPI-REE patients, and much more common than in EoE patients. In contrast, previous systematic reviews did not observe major differences between PPI-REE and EoE patients.…”
mentioning
confidence: 97%
“…SIRS, We thank Drs Molina-Infante et al for taking the time to read our paper, 1 and for their comments. 2 The authors criticise our selection of gastro-oesophageal reflux disesase (GERD) patients and therefore the results of our study.…”
mentioning
confidence: 99%
“…SIRS, We thank Drs Molina-Infante et al for taking the time to read our paper, 1 and for their comments. 2 The authors criticise our selection of gastro-oesophageal reflux disesase (GERD) patients and therefore the results of our study.…”
mentioning
confidence: 99%